2018
DOI: 10.1097/sle.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technique of Distal Roux-en-Y Gastric Bypass for Insufficient Weight Loss After Primary Procedure: Personal Experience and Primary Results at 12 Months

Abstract: In our experience, our DRYGBP differentiated procedure seems to be effective at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Three studies performed routine operations concomitant to LD, including prophylactic cholecystectomy, 2 prophylactic appendectomy, 8 and therapeutic cholecystectomy for chronic cholecystitis 4 . Three studies used marking sutures to discriminate between the intestinal limbs 2,6,16 . Six studies reported measurement of the whole bowel length 5,16–18,20,21 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies performed routine operations concomitant to LD, including prophylactic cholecystectomy, 2 prophylactic appendectomy, 8 and therapeutic cholecystectomy for chronic cholecystitis 4 . Three studies used marking sutures to discriminate between the intestinal limbs 2,6,16 . Six studies reported measurement of the whole bowel length 5,16–18,20,21 .…”
Section: Resultsmentioning
confidence: 99%
“…Operative variations included the type of LD, method of bowel measurement, added restrictive maneuvers, and concomitant operations. Six studies reported measurement of the whole bowel length 5,16–18,20,21 . Total bowel measurement at the beginning of the procedure and the measurement of the 3 limbs (RL, biliopancreatic limb, CL) at the end of the procedure are essential to allow accurate reporting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations